1979
DOI: 10.1046/j.1537-2995.1979.19580059804.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prolonged Room Temperature Holding of Whole Blood Intended for Preparation of Components

Abstract: Current FDA regulations require that platelet concentrates must be prepared within four hours of whole blood collection. To determine if this time period was critical for the harvesting of viable platelets and other blood components, whole blood was held at room temperature for four, six or eight hours after which various components were prepared. Our results indicate that up to eight hours storage had no detrimental effect on platelet yield, recovery in vivo or lifespan. AHF activity, supernatant hemoglobin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…The results of other studies [12][13][14][15][16][17] also show that 6-18 h delay in blood processing has no significant effect on fur ther platelet storage (in these studies PCs were prepared Extracellular elastase activity was found to be similar be tween different stored PCs: 19.5± 17.2 nmol/min (PCs from fresh blood, n = 10), 26.9± 11.8 (overnight-stored blood, n = 10), and 18.7±14.0 (overnight-stored buffy coat, n = 30), respectively.…”
Section: Resultsmentioning
confidence: 92%
“…The results of other studies [12][13][14][15][16][17] also show that 6-18 h delay in blood processing has no significant effect on fur ther platelet storage (in these studies PCs were prepared Extracellular elastase activity was found to be similar be tween different stored PCs: 19.5± 17.2 nmol/min (PCs from fresh blood, n = 10), 26.9± 11.8 (overnight-stored blood, n = 10), and 18.7±14.0 (overnight-stored buffy coat, n = 30), respectively.…”
Section: Resultsmentioning
confidence: 92%
“…No difference in the in vivo recovery and life span of platelets was found when platelets were separated immediately or after a 6-or 8-hour delay [4,5,7], Avoy et al [7] stated that it would not be expected that extending the preparation period of platelets would have any demonstrable effect on platelet function and viability. As might also be expected, the platelet yield was unaf fected.…”
Section: Discussionmentioning
confidence: 99%
“…Current FDA regulations require that platelet con centrates shall be separated within 4 h after collection of the unit of whole blood or plasma [1], This period was increased to 6 h with the 9th edition of the AABB stan dards [2], Regional blood centers using mobile collection teams have logistic problems preparing platelet concen trates within this time. Several in vitro and in vivo studies have shown that an 8-hour delay in the processing of blood did not adversely affect platelets preserved in CPD, CPDA-1 or CPDA-2 [3][4][5]. It has also been shown that human red blood cells tolerate exposure to room temper ature for as long as 8 h without greater loss of ATP or viability than in cells refrigerated within 4 h of phleboto my [6][7][8][9].…”
Section: Methodsmentioning
confidence: 99%
“…Other workers have already demonstrated that red cell and platelet preparations may be prepared up to 8 [6,[9][10][11][12][13][14][15] or 15 h [ 16] after collection of blood in CPD anti coagulants. The in vitro data presented here indicate that red cell and platelet preparations of good quality may be prepared 18 h after collection in 0.5 CPD.A2.…”
Section: Red Cell Preparationsmentioning
confidence: 99%